Sialorrhea with Neurological Diseases in Oral Medicine Fields: A Narrative Review - Ernawati, Diah Savitri; Pasaribu, Togu Andrie Simon (Faculty of Dental Medicine Universitas Airlangga, 2022)
Background: Sialorrhea also known as drooling, literally means excessive saliva flow. In patients with neurological conditions such as Parkinson's disease, cerebral palsy, and stroke. drooling or sialorrhea conditions can be a problem in their lives. In patients with neurological disorders, they experience impaired coordination of facial and mouth muscle movement. Purpose: To describe a review comprehensive management of sialorrhea in neurological, then quality of life can be improved. Reviews: literature search was done thorough literature search between 2008-2020 was done using Science direct, Pubmed and Google Scholar. Conclusion: Treatment for sialorrhea includes non-medical therapy, medical therapy, botulinum toxin, radiotherapy and surgical treatment. Oral medicine specialist dentists have a role in the care of sialorrhea patients with neurological disorders in terms of oral care related as a result of sialorrhea such as perioral dermatitis.